Mobile clouds exploiting distributed resources in wireless networks - Fitzek, Frank H.P; Katz, Marcos D. (Wiley, 2014)
This book discusses and explores the concept of mobile cloud, creating an inspiring research space for exploiting opportunistic resource sharing, and covering from theoretical research approaches to the development of commercially profitable ideas.